2016
DOI: 10.5194/acp-16-14599-2016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sensitivity of the hydroxyl radical to model biases in composition and temperature using a single-column photochemical model for Lauder, New Zealand

Abstract: Abstract. We assess the major factors contributing to local biases in the hydroxyl radical (OH) as simulated by a global chemistry-climate model, using a single-column photochemical model (SCM) analysis. The SCM has been constructed to represent atmospheric chemistry at Lauder, New Zealand, which is representative of the background atmosphere of the Southern Hemisphere (SH) mid-latitudes. We use long-term observations of variables essential to tropospheric OH chemistry, i.e. ozone (O 3 ), water vapour (H 2 O),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Montzka et al (2011) attribute the high interannual variability from previous studies to large uncertainties in the emissions of MCF and methane. The previously mentioned work of López-Comí et al (2016) found no significant trend in OH between 1994 and 2010, based on their single column analysis in the remote southern Pacific Ocean. Two recent chemical inversion studies indicate increases in [OH] TROP by~7%-10% between the 1990s and early 2000s, leading to the plateau in methane growth rate during this time, but differ in their attribution of the rise in methane burden since 2007 (Rigby et al, 2017;Turner et al, 2017).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Montzka et al (2011) attribute the high interannual variability from previous studies to large uncertainties in the emissions of MCF and methane. The previously mentioned work of López-Comí et al (2016) found no significant trend in OH between 1994 and 2010, based on their single column analysis in the remote southern Pacific Ocean. Two recent chemical inversion studies indicate increases in [OH] TROP by~7%-10% between the 1990s and early 2000s, leading to the plateau in methane growth rate during this time, but differ in their attribution of the rise in methane burden since 2007 (Rigby et al, 2017;Turner et al, 2017).…”
mentioning
confidence: 77%
“…Strode et al (2015) found that substituting observed values of ozone and reanalysis values of water vapor for the simulated ones improved their estimate of the methane lifetime using a chemistry-climate model. López-Comí et al (2016) used a single-column photochemical model to determine that water vapor and ozone biases within a global chemistry-climate model have the largest impact on OH over New Zealand. Finally, Nicely et al (2017) showed that the primary causes of variations in [OH] TROP simulated by global models were, in order of importance, different chemical mechanisms, various treatments of the photolysis frequency of O 3 that leads to production of O( 1 D), and modeled O 3 and CO.…”
mentioning
confidence: 99%
“…Global Biogeochemical Cycles estimates, and emissions inventories (i.e., for reactive gases which participate in the formation of OH). Recent studies have quantified sensitivities of global model [OH] to various inputs and parameterizations, which may help modelers better understand how global [OH] simulations could be improved in future (López-Comí et al, 2016;Nicely et al, 2017;Ryan et al, 2018). Alternatively, more comprehensive observations of key tropospheric gases (e.g., O 3 and H 2 O) may allow estimation of [OH] variability using relatively simplified chemical schemes (e.g., Nicely et al, 2018).…”
Section: 1029/2018gb006065mentioning
confidence: 99%